2016
DOI: 10.1186/s12870-016-0762-z
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the significance of cell wall polymers in flax infected with a pathogenic strain of Fusarium oxysporum

Abstract: BackgroundFusarium oxysporum infection leads to Fusarium-derived wilt, which is responsible for the greatest losses in flax (Linum usitatissimum) crop yield. Plants infected by Fusarium oxysporum show severe symptoms of dehydration due to the growth of the fungus in vascular tissues. As the disease develops, vascular browning and leaf yellowing can be observed. In the case of more virulent strains, plants die. The pathogen’s attack starts with secretion of enzymes degrading the host cell wall. The main aim of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 62 publications
2
32
1
Order By: Relevance
“…The higher expression of 3deoxy-d-arabino-heptulosonate-7-phosphate synthase and polyphenol oxidase highlighted the timely recognition of FOP invasion and induction of the defense system [9,18]. These results confirmed that upon infection and establishment of FOP in common bean root tissues, the FOP secreted enzymes loosen and degrade the cell-wall i.e., pectin, cellulose, and hemicellulose [34].…”
Section: Structural Defense In Response To Fop Infection In Common Beansupporting
confidence: 57%
“…The higher expression of 3deoxy-d-arabino-heptulosonate-7-phosphate synthase and polyphenol oxidase highlighted the timely recognition of FOP invasion and induction of the defense system [9,18]. These results confirmed that upon infection and establishment of FOP in common bean root tissues, the FOP secreted enzymes loosen and degrade the cell-wall i.e., pectin, cellulose, and hemicellulose [34].…”
Section: Structural Defense In Response To Fop Infection In Common Beansupporting
confidence: 57%
“…Others have used transgenics to modulate secondary metabolites (carotenoid and flavonoid biosynthesis) to increase resistance of flax to the pathogen, using the antioxidant action of these compounds against the reactive oxygen species produced upon infection (Lorenc-Kukuła et al, 2007, 2009; Boba et al, 2011). Likewise, studies of the behavior of cell wall modification genes and the metabolism of lignin production upon fusarium inoculation showed that some genes are modulated to increase resistance while others might be manipulated by the pathogen (Hano et al, 2006; Wojtasik et al, 2011, 2016). Techniques that have been applied to study these processes include: transformation (Wróbel-Kwiatkowska et al, 2004; Lorenc-Kukuła et al, 2007, 2009; Boba et al, 2011), tissue culture (Rutkowska-Krause et al, 2003), and QTL analysis (Spielmeyer et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a number of studies have found that the PAL gene exhibits a rapid response in the early stages of pathogen infection [4]. However, expression of the PAL gene in flax showed a pattern of continuous increase during pathogen infection [81]. In brief, the PaPAL gene can be induced by Lophodermium piceae, and we speculated that PaPAL plays an active role in the defense against needle cast disease.…”
Section: Discussionmentioning
confidence: 85%